A new species of Microlepidogaster (Loricariidae: Hypoptopomatinae) from rio Pardo, a coastal drainage in eastern Brazil - Martins, Fernanda O. (Zootaxa, 2022)
A new species of Microlepidogaster is described from rio Pardo drainage, a coastal basin in eastern Brazil. This species can be differentiated from its congeners by having the following unique features: 1) anterior portion of snout with a large odontode-free band extending laterally from the anterior tip of snout to the postrostral plate 2; 2) transverse process of second dorsal-fin pterygiophore exposed and bearing odontodes; and 3) exposed area of pectoral girdle extended to the mesial symphysis, with odontodes mainly distributed in the coracoid ventral expansion. The new species is further distinguished by several other morphological non-exclusive features. Recently, some Microlepidogaster species were reallocated to Rhinolekos. The taxonomic changes involving these genera is herein discussed.